Anthropometric characteristic of female junior national team volleyball players: a comparative study - Vasileva, F.; Vasilev, A. (Slovak Journal of Sport Science, 2021)
Introduction Athlete's anthropometric and physical characteristics may represent important pre-requisites for successful performance in volleyball. Thus, the objective is to compare Macedonian Junior National Team players with National Team players from other countries in terms of anthropometric characteristics, in a qualitative manner.